Korelasi Motivasi Belajar Terhadap Hasil Belajar Fisika Siswa Kelas X SMA Negeri 3 Kota Sungai Penuh - Nurmaliza Nurmaliza; Farradilla Handayani; Nabilla Eka Wijaya; Sisca Agustin (Universitas PGRI Semarang, 2020)
The purpose of this research is to determine the effect of learning motivation on student learning outcomes of class X MIPA 4 in SMA Negeri 3 Sungai Penuh City. This type of research is quantitative research with a descriptive approach. Data collection techniques in this study used questions with 25 items with straight motion material changing regularly. The population of this study was students of class X MIPA 4 in SMA Negeri 3 Sungai Penuh City. The sampling technique uses random sampling techniques. The method used in this research is Descriptive Statistics. The data analysis requirements test used were normality test, homogeneity test, and correlation test. Based on the results of this study, it shows that there is a significant positive influence between the student's motivation to learn physics in class X MIPA 4 on learning outcomes in straight motion material changes regularly.